Discover how IDNLearn.com can help you learn and grow with its extensive Q&A platform. Ask anything and receive comprehensive, well-informed responses from our dedicated team of experts.
Sagot :
Answer:
The two functions are inverses.
Step-by-step explanation:
Recall what an inverse is:
When you inverse an equation, like y = 2x for example, you switch, the y and x values. So you'd now have x = 2y, then x/2 = y.
In a case like that we'd say that, y = 2x, and y = x/2 are inverses of each other.
Now looking at your question, all we'd need to do is take the inverse of 1, and see if it matches up with the other one. So pick a function. I'll choose g(x) and I'll inverse it.
[tex]g(x) = y = 2x + 6[/tex]
get rid of the g(x), as it doesn't help you anymore.
[tex]y = 2x + 6[/tex]
then, switch the x and the y.
[tex]x = 2y + 6[/tex]
then isolate for y.
[tex]x - 6 = 2y[/tex]
[tex]\frac{x-6}{2} = y[/tex]
Now let's see, does [tex]f(x) = \frac{1}{2}x - 3[/tex] equal [tex]\frac{x-6}{2}[/tex] ? Well actually yes.
We just didn't simplify all the way.
[tex]\frac{x-6}{2} = y\\[/tex]
divide each term by 2
[tex]\frac{x}{2} - 3 = y[/tex]
[tex]\frac{x}{2}[/tex] can be written as [tex]\frac{1}{2}x[/tex] so we get
[tex]\frac{1}{2}x - 3[/tex] which is equal to f(x)
Therefore the 2 functions are inverses.
Q.E.D
We are happy to have you as part of our community. Keep asking, answering, and sharing your insights. Together, we can create a valuable knowledge resource. IDNLearn.com is your reliable source for accurate answers. Thank you for visiting, and we hope to assist you again.